RULES FOR USING PERSONAL PRONOUNS ARTIFICIAL INTELLIGENCE IN TRANSLATION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article outlines key rules for using personal pronouns, including subject-verb agreement, possessive and reflexive forms, gender and number agreement, and usage after prepositions. It also highlights historical and cultural influences on English, showing how borrowing and globalization have shaped pronoun usage. Understanding these rules ensures clear and grammatically correct communication.